IMPLEMENTASI SISTEM INFORMASI PELATIHAN DAN PENINGKATAN SUMBER DAYA MANUSIA PADA PT. PUPUK KUJANG CIKAMPEK - Lies Nurhayati; Didih Aditiyawarman (Bianglala Informatika, 2018)
Technological advances the world continues to evolve significantly. A set of tools such as computer experts deliberately created in order to facilitate the human work, one of them is in employee training with e-learning system. E-Learning is a concept of the use of electronic applications to support teaching and learning with the Internet media as well as computer networks. This concept carries influence in the transformation process of conventional education to digital form, both the content and the system. Learning system will be replaced with web-based training media.   PT Pupuk Kujang Cikampek requires the presence of an information system to support internal training activities were held continuously every year even every month. System management training existing at PT. Pupuk Kujang Cikampek is still done manually, from training proposal letter writing, recording a list of participants, until the storage of other data related to training activities. It possible during the process there was an error in recording, lack of accurate data as well as the delay in the search for the required data. So, PT. Pupuk Kujang need the new system to solve the problem in employee training, by built an elearning system. This web can be used as registration system, training, shared resource and assesment about employee training, so the activity can be done easier, efectve and effcient.     Keywords: Employee Training, e-learning, human resource